Coffee, the Body's Natural Immunostimulant to ward off Covid-19 - Eka Ratnawati; Bernadheta Karunia Dwi Oktama; Ekmatra Widya Litani; Mesakh Nugroho (Jurnal Kesehatan, 2021)
The Covid-19 pandemic claimed many lives and has a profound impact on the economic and social sectors. Efforts to naturally increase immunity with herbal ingredients are a practical solution to warding off Covid-19. Coffee is a local potential product from Temanggung that have some health benefits. This literature review aims to examine whether coffee can increase immunity to ward off Covid-19. The literature searching was conducted  using Google Scholar and Pubmed databases with the keywords “coffee, antioxidants, immune and Covid-19”, as well as language restrictions and year of publication. The results showed that coffee contains antioxidants that have the potential effect to fight Covid-19, by maintaining the patency of the respiratory tract. Coffee is suitable to be developed into medicinal preparations and herbal food supplements to increase immunity. Consuming coffee with a certain dose and regularly can maintain body immunity. A healthy lifestyle, with a balanced nutritional diet, maintaining cleanliness, adequate water consumption, exercise, rest and sleep can also increase immunity. As a conclusion, coffee is an antioxidant compound that can be developed into medicinal and food preparations to increase immunity to ward off Covid-19. Further research on coffee and its derivatives as an alternative to herbal therapy is very necessary.